Comparison of Compudose with Ralgro or Synovex-S reimplant programs for finishing steers - Laudert, S.B.; Davis, G.V. Jr. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Finishing yearling steers reimplanted with Synovex-S or Ralgro gained 6.8 and 4.2% faster, respectively, than those implanted with Compudose. However, feed efficiency was not significantly different among treatments. Steers implanted with Compudose gained 5.1% faster and more efficiently than those implanted with a single Ralgro.
Keywords: Beef; Feed efficiency; Implants; Rate of gain